Rational places in extensions and sequences of function fields of Kummer type - Chara, María de Los Ángeles (2011)
In this paper we prove   results on the number of rational places in   extensions of Kummer type over finite fields and give sufficient conditions for non-trivial lower bounds on the number of rational places at each step of   sequences of function fields over a finite field, that we call $(a,b)$-sequences. In the case of a prime field, we apply these results to the study of rational places in certain sequences of function fields of Kummer type.